Hurdles and obstacles in monetary policy communication. A model for the communication between the central bank and markets - Dittrich, Winand H.; Wohlmann, Monika (Utrudnienia i bariery w komunikacji w polityce pieniężnej. Model komunikacji między bankiem centralnym a rynkami, 2020)
Central bank communication has become an essential part of monetary policy in recent years. Against the background of the zero interest rate policy, conventional monetary policy instruments have lost their effectiveness, and the management of market participants’ expectations by means of appropriate communication has become an essential part of monetary policy. In this paper a new model of the communication process between the central bank and financial market players is elaborated, in particular exploring the obstacles and hurdles in the transmission of information from sender to recipient, empirical data are also reported for several stages of the new model. For efficient expectation management, both the selection of information by the central bank as well as the transmission path of this information is important as indirect communication can lead to information distortions. Last but not least, the recipients of the information, as people with a limited capacity and variable readiness to absorb it, play a central role in determining what information actually reaches them. Appropriate communication that takes these obstacles and the recipients’ psychology into account can thus significantly increase the efficiency of monetary policy
Ekonomia XXI Wieku = Economics of the 21st Century, 2020, Nr 23, s. 7-34